GUILLAIN-BARRÉ SYNDROME: CAUSES, EPIDEMIOLOGY, IMMUNOPATHOGENIC MECHANISMS, DIAGNOSIS, EVALUATION, DIFFERENTIAL AND TREATMENT - Marjorie Dayanna Cordova Tapia; Karina Noemí Contreras García; Luis Andrés Álvarez Granda; Carmen Valeria Rojas Rojas; Bayron Mario Viscaino Cuzco; Jennyfer Tatiana Gushque Pallmay; Carla Alexandra Idrovo Idrovo; Bryam Esteban Coello García (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
that is commonly generated by infections. Recent studies have shown a strong relationship between Guillain-Barré syndrome and SARS-CoV-2, making SARS-CoV-2 a potential trigger for GBS. Objective: to detail the current information related to Guillain-Barré syndrome, causes, epidemiology, immunopathogenic mechanisms, diagnosis, evaluation, differential and treatment. Methodology: a total of 42 articles were analyzed in this review, including review and original articles, as well as clinical cases, of which 33 bibliographies were used because the other articles were not relevant for this study. The sources of information were PubMed, Google Scholar and Cochrane; the terms used to search for information in Spanish, Portuguese and English were: Guillain-Barré, peripheral nerves, SARS-CoV-2, nerve roots, epidemics, inflammatory disease of the peripheral nervous system. Results: Approximately 70% of affected individuals show signs of previous illness 1 to 6 weeks before the debut of Guillain-Barré syndrome. GBS post influenza infection is up to 7 times more likely than post-vaccine GBS. The studies reviewed indicate a strong relationship between Guillain-Barré syndrome and SARS-CoV-2, the latter being a potential trigger for GBS. Cerebrospinal fluid (CSF) shows a classic pattern of albuminocytologic dissociation. Generally, most individuals affected with GBS present good prognosis, and about 85 % of those present independent ambulation with recovery; however, significant morbidity is present. Conclusions: Guillain-Barré syndrome can become difficult to diagnose and treat, as its clinical manifestations are heterogeneous. Treatment of GBS can be challenging during periods of infectious outbreaks, as seen in the Zika virus and SARS-CoV-2 epidemics. Since not all individuals affected by this syndrome are labeled as positive for antiganglioside antibodies, more quality research is needed to clarify the role of antiganglioside antibodies in Guillain-Barré syndrome as a secondary origin or phenomenon. In proportion to the evolution of scientific information and knowledge of Guillain-Barré syndrome, the diagnosis, management and prognosis are improving all the time.